Search for higgs and Z boson decays to ϕγ with the ATLAS detector - Aaboud, M. (2016)
A search for the decays of the Higgs and Z bA search for the decays of the Higgs and Z bosons to a φ meson and a photon is performed with a pp collision data sample corresponding to an integrated luminosity of 2.7 fb−1 collected at √ s = 13 TeV with the ATLAS detector at the LHC. No significant excess of events is observed above the background, and 95% confidence level upper limits on the branching fractions of the Higgs and Z boson decays to φ γ of 1.4 × 10−3 and 8.3 × 10−6 , respectively, are obtained